MODEL BIROKRASI PARKINSON DALAM PEMERINTAHAN SUSILO BAMBANG YUDHOYONO (SBY) - Nugraha, Fajar Kuala (Jurnal Transformative, 2017)
This paper explains about huge bureaucracy phenomenon in SBY government era. The huge bureaucracy can be understood as an ineffective government. SBY policy with huge bureaucracy is a form of his political choice in purpose to accommodate his supporters. Parkinson model is usually used in U.S government system. Because of that, when SBY adopted huge bureaucracy model, many critics was pointed to him. Why? Because it is not suitable with spirit of thin structure and rich function.